Exploring the mycorrhizal interactions and deciphering the fungal diversity associated with orchid hybrids from the genus Epidendrum - Hammerbacher, Almuth (University of Pretoria, 2024)
Dissertation (MSc (Microbiology))--University of Pretoria, 2024.